2014
DOI: 10.1007/s10068-014-0202-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a post-packaging pasteurization process on inactivation of a Listeria innocua surrogate in meat products

Abstract: Effects of surface pasteurization on inactivation of Listeria innocua were investigated. Surface temperature, monitored during post-packaging pasteurization, was used to predict the lethality of L. monocytogenes. Temperatures reached 70 o C for lean and fat sausages within 9 min of treatment. An inoculation study validated the efficacy of post-processing and the thermal lethality of L. monocytogenes. Pre-cooked sausage and ham, inoculated with approximately 10 7 CFU/cm 2 of L. innocua, were heated to a surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…For example, to extend shelf life up to 4 times,thermal treatment of ready-to-eat vacuumpacked sausages at a temperature of 80 °C for 20 min. was used.Studies on the use of thermal treatment of readyto-eat sausage products were also carried out in [26]. The study results indicate effectiveness of pasteurization in relation to microbiological safety.…”
Section: ____________________________________________________________...mentioning
confidence: 99%
“…For example, to extend shelf life up to 4 times,thermal treatment of ready-to-eat vacuumpacked sausages at a temperature of 80 °C for 20 min. was used.Studies on the use of thermal treatment of readyto-eat sausage products were also carried out in [26]. The study results indicate effectiveness of pasteurization in relation to microbiological safety.…”
Section: ____________________________________________________________...mentioning
confidence: 99%
“…was used. Studies on the use of thermal treatment of ready-to-eat sausage products were also carried out in [26]. The study results indicate effectiveness of pasteurization in relation to microbiological safety.…”
Section: Establishing Temperature and Time Factors For The Post-pastementioning
confidence: 99%
“…Although RTE meat products are fully cooked, secondary microbial contamination may occur during the post-lethality processing procedures, like slicing prior to the packaging of product (Byelashova et al, 2010) and cause serious health problems (Byelashova et al, 2010;Kalinowski, 2010). Thus, the control of contaminations is critical in meat industry (Ahn, Lee, Knipe, & Balasubramaniam, 2014). In a food factory, even with good cleaning and disinfection procedures, microorganisms may remain on food and nonfood contact surfaces and they will form biofilms (Arnold, 1998;Blackman & Frank, 1996) and contaminate products.…”
Section: Introductionmentioning
confidence: 99%
“…Post-packaging pasteurization (PPP) or post-process heat treatment can be used to eliminate microorganisms resulting from post-processing contamination. Several studies have reported the effects of PPP on inactivation of microbial population in RTE meat products (Ahn et al, 2014;Cooksey, Klein, McKeith, & Blascheck, 1993;Enns et al, 2007;Mangalassary, Han, Rieck, Acton, & Dawson, 2008;Muriana, Gande, Robertson, Jordan, & Mitra, 2004;Muriana, Quimby, Davidson, & Grooms, 2002;Murphy & Berrang, 2002;Zhang, 2013). Few studies have evaluated the shelf life of RTE cured and uncured turkey breast (Pal, Labuza, & Diez-Gonzalez, 2008;Pexara, Metaxopoulos, & Drosinos, 2002) during cold storage.…”
Section: Introductionmentioning
confidence: 99%